2020
DOI: 10.1007/s10388-019-00712-w
|View full text |Cite
|
Sign up to set email alerts
|

Esophagectomy performed at institutes certified by the Japan Esophageal Society provide long-term survival advantages to esophageal cancer patients: second report analyzing 4897 cases with propensity score matching

Abstract: Background It will be important for the Japan Esophageal Society (JES) to show an evident advantage of its institution certification system. To achieve this essential task, we used nationally acquired big data to re-analyze 5-year survival information. Methods In 2008-2009, there were 4897 thoracic esophageal cancer patients who underwent esophagectomy and were registered in the National Database of Hospital-based Cancer Registries. We divided these patients into two groups, those who underwent surgery at an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…[15][16][17] Moreover, a certification system for surgeons and institutes has improved the surgery-related mortality rate and has demonstrated that there is a significantly better 5-year survival rate among cStage II-III thoracic esophageal cancer patients treated with esophagectomy by a board-certified esophageal surgeon at an authorized institute. [12][13][14] An attached regional disparity in medical care was that adjuvant therapy before and/or after esophagectomy for advanced thoracic esophageal cancer was more frequent in metropolitan areas. To find the causes will require additional research, and our present data do not provide an answer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[15][16][17] Moreover, a certification system for surgeons and institutes has improved the surgery-related mortality rate and has demonstrated that there is a significantly better 5-year survival rate among cStage II-III thoracic esophageal cancer patients treated with esophagectomy by a board-certified esophageal surgeon at an authorized institute. [12][13][14] An attached regional disparity in medical care was that adjuvant therapy before and/or after esophagectomy for advanced thoracic esophageal cancer was more frequent in metropolitan areas. To find the causes will require additional research, and our present data do not provide an answer.…”
Section: Discussionmentioning
confidence: 99%
“…The institute certification system for esophageal surgery by the Japan Esophageal Society has contributed to this moderate centralization. 12 , 13 , 14 Performance of large numbers of esophagectomies (high‐volume hospital) has been shown to correlate with better short‐term surgical results (mortality or postoperative complication). 15 , 16 , 17 Moreover, a certification system for surgeons and institutes has improved the surgery‐related mortality rate and has demonstrated that there is a significantly better 5‐year survival rate among cStage II‐III thoracic esophageal cancer patients treated with esophagectomy by a board‐certified esophageal surgeon at an authorized institute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations